How young people perceive brands with purpose through social networks in Spain - Sebastián-Morillas, Ana; Martín Soladana, Irene; Clemente Mediavilla, Jorge (Cuadernos.info, 2023)
This article analyzes how brand purpose can influence the way brands develop their communication strategies to reach young people and the importance given to it to change the world. A self-administered online questionnaire was sent to a sample of 500 students from Spanish faculties of Communication Sciences to find out how important brand purpose is to their communication. The results show that brand purpose is important and should be reflected in brands’ communication strategies so that young people buy them in the future, as the vast majority of them want a better society. It can also be said that in today’s society, brands can use their communication strategies as a means to improve the world. However, many young people do not know what brand purpose means and do not rule out buying products that do not meet the brand’s purpose. Therefore, brands need to put more emphasis on developing clear brand purpose strategies to reach more young people and change society to make the world a better place.